Portfolio similarity and asset liquidation in the insurance industry - Giulio Girardi; Kathleen Weiss Hanley; Stanislava Nikolova; Loriana Pelizzon; Mila Getmansky (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
An important assumption underlying the designation of some insurers as systemically important is that their overlapping portfolio holdings can result in common selling. We measure the overlap in holdings using cosine similarity, and show that insurers with more similar portfolios have larger subsequent common sales. This relationship can be magnified for some insurers when they are regulatory capital constrained or markets are under stress. When faced with an exogenous liquidity shock, insurers with greater portfolio similarity have even larger common sales that impact prices. Our measure can be used by regulators to predict which institutions may contribute most to financial instability through the asset liquidation channel of risk transmission.
urn:nbn:de:hebis:30:3-472363
Keywords: G11; G18; G2; 330; Interconnectedness; Asset Liquidation; Similarity; Financial Stability; Insurance Companies; SIFI